Epistemological Obstacles in Geometry within the Context of Gen Z Digital Culture: Hambatan Epistemologis Geometri dalam Konteks Budaya Digital Gen Z - Hidayat, Abas (CV. Media Publikasi Profesional, 2025)
Geometry demands profound deductive-axiomatic reasoning; however, Generation Z has grown up within a digital culture that prioritizes instant visual information. This study aims to analyze the epistemological obstacles in geometry encountered by Gen Z students resulting from the influence of these digital culture characteristics. This research employs a qualitative descriptive method involving 250 high school students born between 2007 and 2010 in the City and Regency of Cirebon. Data were collected through diagnostic tests and in-depth interviews, then analyzed using Brousseau’s theoretical framework. The results identify a shift in the forms of obstacles: first, visual-perceptual obstacles, where students validate geometric truth solely based on visual appearance, adhering to a